2017
DOI: 10.1177/000313481708300619
|View full text |Cite
|
Sign up to set email alerts
|

Pretrauma Functional Independence Measure Score Predicts Survival in Geriatric Trauma

Abstract: The Functional Independence Measure (FIM) is used by rehabilitation professionals to access disability. The FIM score combines both motor and cognitive parameters to assess a patient's level of required assistance in performing activities of daily living (ADL). The geriatric trauma patient is becoming an increasingly important cohort for trauma services. FIM has been shown to predict discharge outcomes and those at high risk for falls. We hypothesized pretrauma FIM scores may predict survival in the geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our study, the mean age of the participants was 75.8±9.74. Research conducted with geriatric trauma patients found a similar mean age (78±8.2) [21]. Evidence on the association between age and functional dependence is well reported and the risk for dependence increases per year of age [22,23,24].…”
Section: IVmentioning
confidence: 80%
“…In our study, the mean age of the participants was 75.8±9.74. Research conducted with geriatric trauma patients found a similar mean age (78±8.2) [21]. Evidence on the association between age and functional dependence is well reported and the risk for dependence increases per year of age [22,23,24].…”
Section: IVmentioning
confidence: 80%